An introduction to secondary data analysis with IBM SPSS statistics - MacInnes, John, 1956- author (Los Angeles Sage Publications Ltd., 2017)
John MacInnes takes the fear out of statistics for students and helps to raise the standards of their quantitative methods skills, by clearly and accessibly introducing all that's needed to know about using secondary data and working with IBM SPSS Statistics.-- Source other than the Library of Congress.
Secondary data analysis : the evidence is out there -- Understanding the basics of statistics -- Doing secondary data analysis in five minutes -- Getting started with SPSS -- Dealing with data documentation -- Replicating published analyses -- Preparing your data -- Managing and manipulating data -- Introducing linear regression -- Getting started with logistic regression -- Using binary logistic regression -- Practising regression skills with replication -- A look back : how to enjoy 'an avalanche of numbers'.
Includes bibliographical references and index.
Keywords: SPSS (Computer file); Quantitative research--Statistical methods--Computer programs; Mathematical statistics--Data processing; General; Datenanalyse; Datenauswertung; Empirische Sozialforschung; Sekundäranalyse.